Perancangan Sistem Informasi Akademik Menggunakan Framework Laravel Berbasis Web (Studi Kasus SMK Paramarta) - Muhammad Rizky Julianto; Iwan Giri Waluyo (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The development of technology in this era of globalization has grown rapidly and can be seen from the use of assessment information systems in the form of portals in schools to facilitate access to assessment information to all students. One of them is SMK Paramarta South Tangerang, it is time to develop technology in information systems to increase efficiency and productivity for education management. Theprocessing of academic data in this school still uses the Ms. Excel application without a database. As a result, there are many obstacles faced by the school in its academic administrative affairs such as processing student data, teachers, subjects, to student grades. In addition, the presentation of information is still not fast, precise and accurate because the current storage media is still conventional / manual. Academic Information System Design Using Web-Based Laravel Framework is designed using PHP programming language and MySQL database which in the final stage can function to facilitate data processing, for the implementation stage using Unified Modelling Language (UML) which can analyze input data and output data. To ensure the application runs well, two stages of testing are carried out, namely testing white boxes and black boxes in the process of collecting user, student, teacher, subject and testing in the process of displaying student grade reports.